2014
DOI: 10.1136/bmj.g2366
|View full text |Cite
|
Sign up to set email alerts
|

Incretin treatment and risk of pancreatitis in patients with type 2 diabetes mellitus: systematic review and meta-analysis of randomised and non-randomised studies

Abstract: Objective To investigate the risk of pancreatitis associated with the use of incretin-based treatments in patients with type 2 diabetes mellitus.Design Systematic review and meta-analysis.Data sources Medline, Embase, the Cochrane Central Register of Controlled Trials (CENTRAL), and ClinicalTrials.gov.Eligibility criteria Randomised and non-randomised controlled clinical trials, prospective or retrospective cohort studies, and case-control studies of treatment with glucagon-like peptide-1 (GLP-1) receptor agon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
148
1
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(160 citation statements)
references
References 82 publications
4
148
1
7
Order By: Relevance
“…A systematic review and meta-analysis of 55 randomized clinical trials (33,350 patients) indicated an odds ratio (95% CI) for pancreatitis of 1.11 (0.57, 2.17) with incretinbased therapies versus control; estimates calculated by incretin therapy class (GLP-1 receptor agonists or DPP-4 inhibitors) showed similar results (23). In the same study, the authors described results of five observational studies without pooled analysis due to variation in outcome measures and data forms.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…A systematic review and meta-analysis of 55 randomized clinical trials (33,350 patients) indicated an odds ratio (95% CI) for pancreatitis of 1.11 (0.57, 2.17) with incretinbased therapies versus control; estimates calculated by incretin therapy class (GLP-1 receptor agonists or DPP-4 inhibitors) showed similar results (23). In the same study, the authors described results of five observational studies without pooled analysis due to variation in outcome measures and data forms.…”
mentioning
confidence: 61%
“…Four of these observational studies showed no increased risk of pancreatitis associated with incretin exposure, but one (19) linked exenatide or sitagliptin use with a significantly increased odds of acute pancreatitis (use within 2 years vs. no use 2.07 [1. 36,3.13]) (23).…”
mentioning
confidence: 99%
“…Whereas no newly generated beta cells were detected by the activation of GLP-1 signalling alone, GLP-1 was able to facilitate beta cell neogenesis initiated by gastrin, although the reprogramming efficiency in our model was not as high as that of other mouse models [1,13]. It is noted that activation of GLP-1 signalling did not induce pancreatitis and pancreatic dysplasia, suggesting that these safety concerns, which have been reported in previous clinical cases and in vivo studies of incretin-based therapies [14][15][16], were abated in our models. The present findings point to possible future therapies for diabetes via these signalling pathways.…”
Section: Introductionmentioning
confidence: 64%
“…Activation of incretin signalling does not induce pancreatitis or pancreatic dysplasia The activation of incretin signalling was reported to possibly be associated with pancreatitis and pancreatic dysplasia both in humans and animal models, although recent studies support the safety of incretin-based drugs [14][15][16][34][35][36]. To test whether or not increased GLP-1 signalling in the pancreas results in undesired pathologies, pancreases from exo-Glp1r mice were examined microscopically.…”
Section: Resultsmentioning
confidence: 99%
“…A szerzők végkövetkeztetése szerint az inkretintengelyen ható gyógyszerek használata során a pancreatitis incidenciája igen alacsony, a gyógy-szer adása nem növeli a pancreatitis kockázatát. Mindazonáltal ez a vélemény nem tekinthető véglegesnek, a további adatgyűjtés még mindig indokolt [28].…”
Section: Metaanalízisek Eredményeiunclassified